Orchestrating corporate social responsibility in the multinational enterprise - Asmussen, Christian Geisler; Fosfuri, Andréa (Strategic Management Journal, 2019)
Research Summary : Multinational enterprises (MNEs) invest significant resources in corporate social responsibility (CSR), but their attempts to build a global “social brand” may clash with the execution of operational strategies at a subsidiary level. Using a game‐theoretic model, this research addresses the complex interplay of different contingencies that shape the coordination and control challenges facing MNEs when they implement global CSR strategies, including brand spillovers, the risk of public scandals caused by irresponsible behavior, the size of the MNE network, as well as the roles played by nongovernmental organizations and altruistic managers. Challenging the view of CSR as insurance against lapses of responsible conduct, our model shows that investment in social brands helps avoid irresponsible practices across the MNE network, thereby inducing subsidiaries to “walk the talk.” Managerial Summary : Global social brands are increasingly valuable to multinational enterprises (MNEs), which makes the control and coordination of responsible behavior across their network of foreign subsidiaries a relevant managerial challenge. Indeed, lapses of responsible conduct at the subsidiary level often generate reputational damage at the multinational level. This research explores several mechanisms that help MNEs manage this coordination and control challenge. First, it shows under what conditions MNEs can leverage their investments in social brands to induce responsible practices across their global network. Second, it illustrates how MNEs can exploit collaborations with nongovernmental organizations to reduce the costs of coordinating and controlling their subsidiaries. Finally, it identifies conditions under which MNEs benefit from hiring altruistic managers to run their subsidiaries.